Analisis Beban Kerja pada Bagian Produksi Paving Guna Mengoptimalkan Jumlah Produksi pada PT. Pesona Arnos Beton di Gresik - Ramadani, Brian; Siti Muhimatul Khoiroh (SURYA TEKNIKA, 2024)
PT Pesona Arnos Beton is a paving manufacturing company in Kedamean Hamlet, Gresik Regency, East Java. They produce 8 variants of paving with different shapes and sizes. The company has 5 paving machines and 20 workers. In this research, a WorkloadiMeasurementiAnalysis (WLA) was conducted to measure the company's workload. From the results of the calculation of optimizing additionaliproduction capacity, using a normal target involving 20 workers, the companyiis able to produce 51,150 paving pallets with a labor cost of Rp. 462,861,000 in 6imonths. This method isicheaper than using aniovertime target, whichiproduces 55,025 paving pallets by increasing operating hours by 1 hour and a totalicost of Rp. 533,200,000 in 6imonths. By following the productionitarget plan, PT Pesona Arnos Beton can reduce production costs by Rp. 70,339,000.